The Effectiveness of Augmented Reality on Students' Higher Order Thinking Skills (HOTS) in Geography - Ansori, Isa; Arianto, Fajar; Khotimah, Khusnul (research, training and philanthropy institution Natural Aceh, 2025)
This study examines the effect of using Augmented Reality (AR) on improving students' higher-order thinking Skills (HOTS) in the Solar System material at a high school in Surabaya. HOTS includes critical thinking, problem-solving, and logical reasoning skills essential in 21st-century learning. The study uses a pre-experimental design with a one-group pretest-posttest design. Tenth-grade students were selected through purposive sampling and were given multiple-choice tests before and after the AR-based learning intervention to measure their improvement in HOTS. The results show a significant increase in students' HOTS, with an N-gain score of 0.58, which falls into the moderate category. Statistical analysis revealed a significant difference between the pre-test and post-test scores, indicating that AR effectively enhances students' ability to analyze, solve problems, and express their thoughts more clearly and systematically. These findings imply that the application of AR in learning can support an outcome-based education approach. Integrating AR into the curriculum is expected to improve the quality of learning, support the achievement of educational goals, and develop students' critical thinking skills for their future.